الأساس الأخلاقي للمعرفة العلمية في الفلسفة البوبرية - بركات, سليم; سليمان, نداء محمود (Latakia University Journal - Arts and Humanities Sciences Series, 2013)
لقد تناول البحث دراسة تحليلية نقدية للأساس الأخلاقي الذي تُبنى عليه المعرفة العلمية من وجهة نظر فيلسوف العلم المعاصر كارل بوبر، وذلك من خلال تبيان رأيه في كون المعرفة العلمية معرفة ناقصة عندما لا تُؤسس على نهجٍ معرفي ومضمونٍ أخلاقي يحميها من الانزلاق والخطأ، مؤكداً على وجود علاقةٍ وثيقة وارتباطٍ قوي بين المعرفة والأخلاق، فإذا انحرفت مالت معها معيارية العلم بأكملها. أظهرت النتائج أن المعرفة عامة، من حق الجميع امتلاكها، ففيها تكمن الحقيقة، ولبلوغ هذه الحقيقة لابد من اتباع منهجيات عديدة كما يقول بوبر، أهمها النهج النقدي والحوار العقلاني، الذي ندرك بواسطتهما أن الإنسان يخطئ وبالتالي فمعرفته قد تكون خاطئة، وللوصول إلى المعرفة العلمية الحقيقة لابد من الطريق التكذيبي الذي نخضع فيه الفرضية لأنواعٍ مختلفة من الاختبارات. أشار بوبر إلى أن الإنسان المتلقي المتبصر هو الذي يستطيع ممارسة هذه العمليات المنطقية، والإنسان المتبصر هو كائن مسامح بطبيعة الأحوال، غير متعصب، منفتح،ينقد ويقبل أن ينتقده الآخرون، وغير محتكر للمعرفة, وعلى هذا الأساس تُبنى المعرفة على قاعدة، حيث تكون قاعدتها أخلاقية بحتة، ودونها تفقد معناها ومصداقيتها. The research addressed a critical analytical study of the moral basis of scientific knowledge from the viewpoint of the contemporary philosopher of science Karl popper, throughout his opinion on the fact that scientific knowledge is incomplete when not based on cognitive approach and moral content which protect it from slipping and error, stressing the close relationship and the strong correlation between knowledge and ethics, which if deviated affected the standards of science as a whole. Results showed that knowledge, generally, is everyone's right to possess, threr resides the truth, and to reach this truth there must be many methodologies, says popper, the most important of which is the critical approach and rational dialog, by which we realize that the human makes mistakes and, consequently, his knowledge may be wrong, and to access the real scientific knowledge the skeptical approach should be followed in which the premise is tested in different ways. Popper pointed out that the insightful human recipient can exercise these logical operations, and the insightful human is naturaly forgivable non- fanatic, open to criticism, non-monopolistic of knowledge and therefore the basis of knowledge is purely ethical, without which knowledge loses its meaning and credibility.